2003
DOI: 10.1111/j.1651-2227.2003.tb00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological assessment at five years of age in infants born preterm

Abstract: Aim: To evaluate the agreement between Touwen's neurological examination and a derived simplified one, created to be applied at the age of 5 y to infants born preterm. Methods: 185 children born at a gestational age (GA) of <33 wk and/or with a birthweight <1501 g, free of cerebral palsy, underwent Touwen's neurological examination at a mean age of 5 y and 8 mo (5‐6.5 y). One‐hundred and seventy had a full examination and were included into the study. They were born at a mean GA of 30 wk (range 24–35 wk) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…However, the study by Fily et al, 17 , showed good agreement between the two approaches; we are therefore confident that neither prevalence of MND in our sample nor associations with other neurodevelopmental domains were significantly affected by using the simplified version. We showed that in children born extremely preterm the prevalence of MND was significantly higher than in term-born participants, and that this has clinically significant implications for everyday motor function, cognitive abilities, and behaviour.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, the study by Fily et al, 17 , showed good agreement between the two approaches; we are therefore confident that neither prevalence of MND in our sample nor associations with other neurodevelopmental domains were significantly affected by using the simplified version. We showed that in children born extremely preterm the prevalence of MND was significantly higher than in term-born participants, and that this has clinically significant implications for everyday motor function, cognitive abilities, and behaviour.…”
Section: Discussionsupporting
confidence: 54%
“…Neurological profile was assessed with a simplified version of the Touwen Infant Neurological Examination 17 and included the evaluation of four domains: reflexes, nerve function of the face and eyes, posture and muscle tone, and coordination and balance. The findings were classified on the basis of the number of dysfunctional domains, as normal neurology, simple MND (one or two domains abnormal), or complex MND (more than two domains abnormal).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…N indicated normal clusters, MND‐1 one or two dysfunctional clusters and MND‐2 more than two dysfunctional clusters (Fily et al. ). An adapted version of this test was used, adding posture during walking, biceps reflex and muscle tone in the elbows (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…A shortened version with 16 selected items grouped into clusters was used with classifications based on the number of dysfunctional clusters. N indicated normal clusters, MND-1 one or two dysfunctional clusters and MND-2 more than two dysfunctional clusters (Fily et al 2003). An adapted version of this test was used, adding posture during walking, biceps reflex and muscle tone in the elbows ( Table 2).…”
Section: Physical Examination and Clinical Neurological Assessmentmentioning
confidence: 99%